Does obtaining an initial magnetic resonance imaging decrease the reamputation rates in the diabetic foot?. Issue 1 (1st January 2016) - Jbara, Marlena; Gokli, Ami; Beshai, Sally; Lesser, Martin L.; Hanna, Shirley; Lin, Cheryl; Zeb, Annie
Abstract : Objective: Diabetes mellitus (DM) through its over glycosylation of neurovascular structures and resultant peripheral neuropathy continues to be the major risk factor for pedal amputation. Repetitive trauma to the insensate foot results in diabetic foot ulcers, which are at high risk to develop osteomyelitis. Many patients who present with diabetic foot complications will undergo one or more pedal amputations during the course of their disease. The purpose of this study was to determine if obtaining an initial magnetic resonance imaging (MRI), prior to the first amputation, is associated with a decreased rate of reamputation in the diabetic foot. Our hypothesis was that the rate of reamputation may be associated with underutilization of obtaining an initial MRI, useful in presurgical planning. This study was designed to determine whether there was an association between the reamputation rate in diabetic patients and utilization of MRI in the presurgical planning and prior to initial forefoot amputations. Methods: Following approval by our institutional review board, our study design consisted of a retrospective cohort analysis of 413 patients at Staten Island University Hospital, a 700-bed tertiary referral center between 2008 and 2013 who underwent an initial great toe (hallux) amputation. Of the 413 patients with a hallux amputation, there were 368 eligible patients who had a history of DM with documented hemoglobin A1c (HbA1c) within 3 months of the initial first ray (hallux and first metatarsal) amputation and available radiographic data. Statistical analysis compared the incidence rates of reamputation between patients who underwent initial MRI and those who did not obtain an initial MRI prior to their first amputation. The reamputation rate was compared after adjustment for age, gender, ethnicity, HbA1c, cardiovascular disease, hypoalbuminemia, smoking, body mass index, and prior antibiotic treatment. Results: The results of our statistical analysis failed to reveal a significant association between obtaining an initial MRI and the reamputation rate. We did, however, find a statistical association between obtaining an early MRI and decreased mortality rates. Discussion: Obtaining an early MRI was not associated with the reamputation rate incidence in the treatment of the diabetic foot. It did, however, have a statistically significant association with the mortality rate as demonstrated by the increased survival rate in patients undergoing MRI prior to initial amputation.